Blockchain Based Certificate Verification System Management - Aini, Qurotul; Harahap, Eka Purnama; Santoso, Nuke Puji Lestari; Sari, Siti Nurindah; Sunarya, Po Abas (Pandawan, 2023)
One of the key responsibilities of the Public Key Infrastructure is revocation management. Additionally, the security of any Public Key Infrastructure (PKI) depends on it. Today's revocation methods are susceptible to a single point of failure when network traffic rises due to the growth in the quantity and size of networks as well as the adoption of new paradigms like the Internet of Things and the use of the web. The author uses the strength and resiliency of blockchain to overcome these issues and present a productive decentralized certificate revocation management and status verification system. The author adds a field that specifies which distribution point the certificate will belong to in the event that it is revoked using the certificate structure extension field. Then, the author carries out a thorough assessment of our plan using performance indicators like execution time and data consumption to show that it can fulfill the demands with high effectiveness and little expense. Additionally, the author contrasts the effectiveness of our strategy with two of the most widely-used revocation approaches, namely the Certificate Revocation List and the Online Certificate Status Protocol. The data collected demonstrate that our suggested strategy works better than the existing scheme.